1999
DOI: 10.1016/s0960-9822(00)80062-7
|View full text |Cite
|
Sign up to set email alerts
|

The human homologue of Caenorhabditis elegans CED-6 specifically promotes phagocytosis of apoptotic cells

Abstract: A key feature of the process of programmed cell death (apoptosis) is the efficiency with which the dying cells are recognized and engulfed by phagocytes [1]. Apoptotic cells are rapidly cleared either by neighbouring cells acting as semi-professional phagocytes or by experts of the macrophage line, so that an inflammatory response is avoided [2]. The Caenorhabditis elegans gene ced-6 is required for efficient engulfment of apoptotic cells [3] and is one of a group of genes that define two partially redundant p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(48 citation statements)
references
References 18 publications
1
47
0
Order By: Relevance
“…Dock2 appears to be the Dock180 of hematopoietic lineage cells. Dock180 associates with Crk and p130Cas and is an important regulator of Rac, cell migration, and phagocytosis of apoptotic bodies (22,23,(45)(46)(47). Higher-level association of Dock2 with SH2D1A may require factors exclusively expressed in lymphoid tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Dock2 appears to be the Dock180 of hematopoietic lineage cells. Dock180 associates with Crk and p130Cas and is an important regulator of Rac, cell migration, and phagocytosis of apoptotic bodies (22,23,(45)(46)(47). Higher-level association of Dock2 with SH2D1A may require factors exclusively expressed in lymphoid tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Albert and colleagues recently showed that stimulation of αvβ5 vitronectin receptor on DCs activates this pathway, and it is likely that other receptors will be found to activate this pathway (44). It is exciting to note also that ced-6 has a human homologue that is implicated in signaling for uptake in mammalian cells (58)(59)(60)(61). Combining the power of the genetic studies in C. elegans and Drosophila with the recognition and biochemical studies in mammalian cells has allowed the study of apoptotic cell clearance to finally make significant progress.…”
Section: Mechanisms and Consequences Of The Uptake Of Apoptotic Debrismentioning
confidence: 99%
“…106 Since ced-6 has been proposed to act as an adaptor molecule and does not possess an obvious catalytic domain, it is unclear whether it acts upstream or downstream of ced-10. 105,106,133,134 It is possible that the ced-1 pathway signals through an alternative Rac-like GTPase even in the presence of a ced-10 mutation since C. elegans express a Rac2 homologue 135 and a GTPase termed Mig-2 that is 64% identical to ced-10. 136 Interestingly, the scavenger receptor MARCO, which is involved in the macrophage clearance of bacteria, was recently shown to induce morphological changes associated with rearrangement of the actin cytoskeleton when overexpressed.…”
Section: Mammalian Homologues Of Ced Engulfment Genesmentioning
confidence: 99%